Reflections on the Concomitants of the Restrictive Visitation Policy During the COVID-19 Pandemic: An Ubuntu Perspective - Mulaudzi, Fhumulani Mavis; Anokwuru, Rafiat Ajoke; Du-Plessis, Moselene A. R.; Lebese, Rachael T. (Frontiers in Sociology, 2022)
Caregiving is a prominent concept in the ubuntu philosophy and caring and visitation of the sick is regarded as the exhibition of Ubuntu. The restrictive visitation policy adopted in the hospitals during the COVID-19 pandemic affected the exhibition of this concept among patients, nurses and families. The narrative inquiry was used to explore the reflections of the participants on the impact caused by the non-visitation policy experienced during the first and second waves of the COVID-19 pandemic in South Africa. The narrative inquiry approach allowed the participants to tell their story as it is unique to them. The study used purposive sampling technique to select five participants for the webinar. Three themes emerged from the narrated stories which are: Moral anguish of the caregivers; mental health instability and Erosion of trust in health care practitioners. The non-visitation hospital policy was able to reduce the danger of spreading the virus within and outside the hospital; however, the care provided was devoid of the values of ubuntu such as mutual respect, relational, responsibility, reciprocity and interconnectedness. In retrospect, a case by case application of the policy would reduce the non-desirable effect of the policy on the patients, nurses and patients’ family